K voprosu o terminologii v reabilitologii - Kachesov, V. A.; Mikhaylova, Yu. B. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The aim of this study was to substantiate the definitions of "function", "life", "biological death", "regeneration of tissues" in the aspect of rehabilitology's problems.